Hubungan Perilaku Hidup Bersih Dan Sehat (PHBS) Dengan Kesehatan Lingkungan Di Sekolah Dasar Negeri 06 Muaradua Tahun 2023 - Hearisa, Phetri; Meliyanti, Fera; Marita, Yulis (JURNAL SMART ANKes, 2023)
Clean and Healthy Living Behavior in schools was one of the efforts to increase the level of health in schools involving students, and the societies in the school environment to be able to practice Clean and Healthy Living Behavior and play an active role in realizing a healthy school. This research design used quantitative correlation with Cross-Sectional approach where data on both variables were collected at the same time or at one time, In this study, researchers will look for the relationship among knowledge, behavior, and PHBS actions, with Environmental Health in state Elementary School 06 Muaradua in 2023 The population in this study is all grade 3 to grade 5 children in State Elementary School 06 Muaradua totaling 350 students, a sample of 184 students was taken. From the results of the analysis, it was found that the knowledge was negative and the environmental health was negative as many as 70 respondents (73.7%), positive knowledge and negative environmental health as much as 52 (58.4%). The negative attitude and negative environmental health as many as 68 respondents (73.9%), The positive knowledge and negative environmental health as many as 54 (58.7%). The negative actions and negative environmental health were as many as 74 respondents (73.3%).Bivariate results obtained there is a relationship between knowledge and environmental health with a value of 0.042p<0.05. There is a significant relationship between attitude and environmental healthvalue 0.043` or p value < 0.05. There is a meaningful relationship between action and healthenvironment with a value of 0.041 or a p value <0.05. There is a significant relationship between knowledge, attitudes and actions environmental health.